Record Setting Temperatures in the Setting of SARS-CoV-2 Suggests Dexmedetomidine Drug-Induced Fever: A Case Report - Megan Meier PharmD, BCPS; Becky S Linn BA, PharmD, BCPS (SAGE Publishing, 2024)
Patients infected with COVID-19 can develop coinfections or acute respiratory disorder that result in ventilation. Dexmedetomidine is a common medication used to sedate ventilated patients in the intensive care unit and for nonintubated patients prior to a surgical procedure. As a highly selective alpha-2 agonist, dexmedetomidine provides sedation while reducing the need for anxiolytics or opioids. However, previous case reports suggest dexmedetomidine can induce fever in a variety of conditions. The purpose of this case report is to describe a patient who acquired a fever of 42.6°C in the setting of COVID-19 after administration of dexmedetomidine.